Aplicación de un sistema de costos por procesos en la florícola “Flores Toacaso S.A” en el periodo comprendido entre el 01 de enero al 31 de julio del 2013, ubicado en la provincia de Cotopaxi cantón Latacunga parroquia Toacaso - Sanchez Cizapanta, Veronica del Carmen (2014)
This thesis was developed in the enterprise named Flores Toacaso SA. Its aim was to maximize the benefits for this enterprise, optimize resources, materials and production costs throughout the implementing of protection measures and providing an added value to the product in order to satisfy customers. This will make the enterprise create a quality, health and innovation image. The enterprise evaluated, is considered as a micro enterprise by its daily production and marketing which looks for, through the automation of its processes, achieving an increase of the product demand in order to be leader in the market place. Therefore, the implementation of a System Costs for Process for the enterprise Flores Toacaso S.A was recommended. This will allow determining the actual value of each stage of the production process by reducing raw material, labor and manufacturing overhead costs which are important factors for calculating the unit cost of different goods produced. By using this system, it is possible to control the appropriate management of the various areas of production and all resources which results in increasing profitability and productivity in the market. This will allow ensuring efficient decision making of the representatives. Further, financial statements are designed in correspondence with the structure of NIIF, with their data, showing the actual movements done during the time mentioned. This will help to interpret and analyze the current situation of the enterprise.